Beyond Detection: The Development of SIJORA and Mitigating Iatrogenic Risks in Adolescent Online Gambling Screening - Husna, Aftina Nurul; Kuswardani, Hasna' Pratiwi; Rahmawati, Adelina; Hendriyani, Rulita (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: As online gambling among Indonesian adolescents reaches crisis proportions, the lack of culturally sensitive screening tools hinders effective intervention. This study develops the Skrining Judi Online Remaja (SIJORA) by adapting the SOGS-RA through a rigorous qualitative validation framework. Beyond establishing content and response process validity via cognitive interviews and expert reviews, our research identifies a critical iatrogenic risk: traditional single-stage screening can trigger negative reactance among non-gambling youth. To mitigate this, we propose a novel Two-Stage Screening Protocol: a primary universal filter followed by a targeted clinical severity assessment. This dual-layered design maximizes diagnostic sensitivity while upholding the ethical principle of "do no harm" in school-based settings. Our findings establish SIJORA as a foundational, ethically-grounded instrument for mental health practitioners and provide a strategic roadmap for the consequential validity of behavioral addiction screenings in the Global South  Keywords: adolescents online gambling screening, qualitative approach, instrument development, content validation, response process validation